IMPLEMENTASI SAK EMKM (ENTITAS MIKRO, KECIL DAN MENENGAH) PADA UMKM BORNEO FOOD TRUCK SAMARINDA COMMUNITY - Ivana Nina Esterlin ,Andi Indrawaty ,Danna Solihin (RJABM (Research Journal of Accounting and Business Management), 2018)
At present the development of business world is increasingly rapid in Indonesia. However, the problem with EMKM is that there are not many EMKMs that are able to hold records, bookkeeping, and even financial reporting.Borneo Food Truck Samarinda Community have not been able to carry out and implement recording, bookkeeping, and financial reporting in their entities. The research objectives to be find out whether Borneo Food Truck Samarinda Community can implement this SAK EMKM in 2018 and to find out the obstacles faced in implementing the SAK EMKM in Borneo Food Truck Samarinda. The research method used is qualitative research. Data collection techniques using interview techniques, documentation and observation. The result showed that of the thirty three UMKM Borneo Food Truck Samarinda Community respondents there were ten UMKM that made journals, inventory data, sales data and prepared financial reports and twenty three UMKM that did not make accounting records.